PERADABAN DAN PEMIKIRAN ISLAM DI INDONESIA - A. Batubara, Khodijah Zuhro; Daulay, Haidar Putra; Dahlan, Zaini (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2021)
Compared to other countries in Southeast Asia, Indonesia is a great reflection of ethnicity, language and culture. Almost all major religions grow here. Various ethnic groups and residents live in a very tolerant spirit. Foreigners who arrived here and then stayed, especially Arabs, Persians, Indians, Chinese and Europeans, were welcomed with open arms and quickly integrated into the population of the entire archipelago. This discussion uses a type of library research approach. As for the results in terms of civilization, there were three ministerial decrees in 1975, two ministerial decrees in 1984, and madrasah madrasas from UUSPN, MI, MT, MA to major academies such as UIN, IAIN, STAIN in 1989. What is. Not only junior high school, but also high school and other major academies such as UI, UNJ, ITB, UNPAD, UPI, UGM, UNDIP. Pesantren, from traditional pesantren to modern pesantren, are also developing productively in both urban and rural areas. From the perspective of thought, namely Starting from the replenishment of Islamic learning ideas in Minankabau, following the revival of learning pursued by the Middle East in Indonesia, the Islamic revival has grown into a social organization, a socio-religious organization such as Salekat Dagan Islam (SDI) Bogor. (1909)) and Solo (1911) and others.